Community perspectives of Ebola Viral Disease in high-risk transmission border regions of Tanzania: a qualitative inquiry - Emmy Metta; Hussein Mohamed; Priscilla Kusena; Tumaini Nyamhanga; Shalini Bahuguna; Deodatus Kakoko; Nathanael Siril; Awet Araya; Alice Mwiru; Stanley Magesa; Lulu Makene; Allan Rwechungura; et al. (BMC, 2024)
Abstract Background Tanzania faces ever-rising concerns due to the recurrence of the Ebola Virus Disease (EVD) in neighbouring Democratic Republic of Congo (DRC) and Uganda. This necessitates a better understanding of the community perspectives in high-risk regions for effective risk communication and preparedness. Methods This rapid ethnographic assessment study used explorative qualitative methods to collect data. People from diverse backgrounds participated in 59 in-depth interviews, 57 Key Informant interviews, and 35 focus group discussions. Data was analysed using a thematic analysis approach. Finding The study revealed existence of awareness of EVD and its symptoms, with radio and television being the main sources of information. However, there were varied perceptions of EVD's cause and transmission, some attributed it to bats, monkeys, and wild animal meat, while others associated it with high fever, a dirty environment, changing dietary patterns, and the COVID-19 virus. Physical contact with an infected person's body fluids and eating meat from infected animals were perceived as EVD transmission routes. Women, school children, boda-boda (motorcycle) riders, and fishermen were considered the most susceptible to EVD infections due to their daily activities. Preventive measures included avoiding physical contact, touching fluids, and refraining from eating wild animal meat. Prompt reporting of suspected cases to health facilities was deemed crucial for earlier outbreak identification and containment. Conclusion The high-risk regions of Tanzania had a high level of awareness and perceived susceptibility to EVD, coupled with varying degrees of misperception about the etiology and its transmission. To improve community perspectives and preparedness in the case of an outbreak, there is a need for ongoing risk communication and participation in EVD prevention and responses.